Humeral lengthening and deformity correction - Hosny, Gamal Ahmed (J Child Orthop, 2016)
INTRODUCTION: Ilizarov principles and hybrid fixation have improved the results of humeral lengthening. We reviewed the literature on humeral lengthening using different fixators with regard to indications, operative technique, results and complications. We also retrospectively reviewed 56 segments in 46 patients treated with humeral lengthening and deformity correction using Ilizarov external fixation. The etiology was achondroplasia (10 patients), epiphyseal injury (8 cases), infection (11 cases) and Erb’s palsy (17 cases). The average age at surgery was 14 years (range 8–20 years). The patients were assessed clinically and radiographically and DASH score was available for 36 segments. Follow-up ranged from 1−11 years. The magnitude of lengthening achieved ranged from 5−15.5 cm with an average of 9 cm. The average healing index was 29.5 cm (range 26–37 days). The percentage of area of lengthening to the original length ranged from 25 to 100% with an average of 55%. The average DASH (available for 36 segments only) score ranged from 15−40 preoperatively to 7−16 (P = 0.04) at last follow-up. Functionally, all the patients returned to their preoperative jobs and daily activities including sports. COMPLICATIONS: Complications included pin track infection in 46 segments, radial nerve palsy which recovered completely in 2 patients, fracture of the regenerate in 7 cases and premature consolidation of the regenerate in one case. CONCLUSION: Humeral lengthening, whether unilateral or bilateral, is a valid method that improves the outcome following arm shortening and deformity correction, including angulation and rotation. Extensive lengthening up to 100% of the original length could be achieved without increasing the risk of complications. LEVEL OF EVIDENCE: IV, retrospective cohort.